2021
DOI: 10.3390/su131810097
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Carbon Footprint of Biochar from Willow Grown on Marginal Lands in Finland

Abstract: Willow biochar can help to sequestrate carbon. However, biomasses should not be grown on arable lands, as it would increase competition with food production and lead to sustainability issues such as increased food prices and decreased food security. The purpose of this study is to calculate the carbon footprint (CF) of willow biochar in Finland and assess the greenhouse gas compensation potential of marginal lands if they are utilized for willow biochar production. The CF of willow biochar is inadequately asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…5a). Similarly, Leppäkoski et al (2021) calculated the carbon footprint of willow biochar production and application in marginal lands by conducting a cradle-to-grave LCA. Their results found that the carbon footprint of willow biochar was − 1875 kg CO 2e t −1 , in which carbon sequestration (− 1704 kg CO 2e t −1 ) dominated the carbon footprint.…”
Section: Biochar For Global Climate Change Mitigationmentioning
confidence: 99%
“…5a). Similarly, Leppäkoski et al (2021) calculated the carbon footprint of willow biochar production and application in marginal lands by conducting a cradle-to-grave LCA. Their results found that the carbon footprint of willow biochar was − 1875 kg CO 2e t −1 , in which carbon sequestration (− 1704 kg CO 2e t −1 ) dominated the carbon footprint.…”
Section: Biochar For Global Climate Change Mitigationmentioning
confidence: 99%
“…Accepting the application of willow biochar in the entire area of agricultural arable land in the current territories, as well as knowing that Willow biochar could compensate 7.7 % of annual agricultural greenhouse gas emissions [86], however, in 2018, soil cultivation in Latvia generated 1547.4 kt CO2eq emissions [87], which was the largest sub-sector of GHG emissions in the agricultural sector in terms of emissions. It can be seen that the possibilities of sequestration could be as much as 119 kt CO2eq per year, but it should be noted that this calculation is idealized without in-depth research on those areas where such application of willow biochar would not be desirable.…”
Section: Methodsmentioning
confidence: 99%
“…Their use offers both environmental and economic benefits, including improvement of soil quality, ecosystem restoration, and sustainable bioenergy production (Volk et al 2004;Christersson 2011;González-García et al 2012;Isebrands et al 2014;Gkorezis et al 2016;Asad et al 2017;Ziegler-Devin et al 2019;Hepner et al 2021;Eadha 2022;Kaivapalu et al 2023). For example, in Finland, it has been estimated that Salix biochar production from all marginal lands could offset 7.7% of yearly agricultural greenhouse gas emissions (Leppäkoski et al 2021).…”
Section: Joensuu January 2024mentioning
confidence: 99%